2017
DOI: 10.5812/jost.63868
|View full text |Cite
|
Sign up to set email alerts
|

Floating Hip, Eleven Cases and Literature Review

Abstract: Floating hip refers to concomitant fracture of the acetabulum, pelvis, and femur. We report the cases, our approach, as well as short-term results from 2008 to 2016. There were a total of 11 cases. The most prevalent pelvis fracture type were Tile type C and the most acetabulum fractures were both column fracture. The most femoral side fractures were per-throchantrric fractures (head, neck, intertrochanteric fracture). In most cases, fixation started from the pelvis, acetabulum, and then the femur. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Iatrogenic sciatic nerve (7) have reported that males were affected more than females in their respective studies. Muller et al (6) and Siavashi (13) had almost an equal number of patients of each gender. The almost exclusive male involvement in our series can be attributed to their greater outdoor exposure as compared to the females in our region.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Iatrogenic sciatic nerve (7) have reported that males were affected more than females in their respective studies. Muller et al (6) and Siavashi (13) had almost an equal number of patients of each gender. The almost exclusive male involvement in our series can be attributed to their greater outdoor exposure as compared to the females in our region.…”
Section: Resultsmentioning
confidence: 98%
“…Surgical stabilization helps in rehabilitation and an early return to productivity. While Liebergall et al (5) preferred operating first on the femur, Siavashi (13) managed 10 out of their 11 patients by operating first on the pelvi-acetabular fractures. Suzuki et al (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation